2013
DOI: 10.1186/1472-6955-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and partners’ health-related quality of life before and 4 months after coronary artery bypass grafting surgery

Abstract: BackgroundPatients having coronary artery bypass grafting (CABG) often depend on their partners for assistance before and after surgery. Whilst patients’ physical and mental health usually improves after surgery little is known about the partners’ health-related quality of life (HRQoL) in CABG. If the partners’ physical and emotional health is poor this can influence their caregiving role and ability to support the patient. This study aimed: to increase understanding of patients’ and partners’ HRQoL before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
(107 reference statements)
1
20
0
Order By: Relevance
“…The concept that encompasses QOL is broad ranging, and is affected in a complex way by the person's physical health, psychological state, personal beliefs, social relationships and their relationship to salient features of their environment (WHO, 2004). Within the context of QOL, the CABG has shown to improve the quality of a person's life by being effective in preventing mortality , saving lives and reducing angina (V. M. Peric, Borzanovic, Stolic, Jovanovic, & Sovtic, 2006;Thomson, Niven, Peck, & Eaves, 2013). This is supported by several studies that reported post-CABG improvement of patients' quality of life (Taghipour et al, 2011;Thomson et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The concept that encompasses QOL is broad ranging, and is affected in a complex way by the person's physical health, psychological state, personal beliefs, social relationships and their relationship to salient features of their environment (WHO, 2004). Within the context of QOL, the CABG has shown to improve the quality of a person's life by being effective in preventing mortality , saving lives and reducing angina (V. M. Peric, Borzanovic, Stolic, Jovanovic, & Sovtic, 2006;Thomson, Niven, Peck, & Eaves, 2013). This is supported by several studies that reported post-CABG improvement of patients' quality of life (Taghipour et al, 2011;Thomson et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…Within the context of QOL, the CABG has shown to improve the quality of a person's life by being effective in preventing mortality , saving lives and reducing angina (V. M. Peric, Borzanovic, Stolic, Jovanovic, & Sovtic, 2006;Thomson, Niven, Peck, & Eaves, 2013). This is supported by several studies that reported post-CABG improvement of patients' quality of life (Taghipour et al, 2011;Thomson et al, 2013). For instance, Anderson & Buckhardt (1999) has shown that about 90% of post CABG patients experienced significant improvement of quality of life (QOL) in their research.…”
Section: Introductionmentioning
confidence: 99%
“…The median sample size across studies was 124 (range 34–734), and the mean age of caregivers enrolled was 61 years (range 37–82). Across the observational studies, we identified similar themes as found in the qualitative studies: caregiver work challenges (n=6)33–37; caregivers’ adaption to recovery including emotional responses (n=9)35 37–44; caregiver stress (n=4),41 43–48; caregivers’ health-related quality of life (HRQoL) (n=9) 36 45–52. Thirteen studies also explored caregiver experiences of social support 37–39 42 43 45 46 49 51–55.…”
Section: Resultsmentioning
confidence: 68%
“…Partners reporting poorer emotional, physical and social functioning postoperatively were associated with patients who had poorer preoperative mental health. Poorer postoperative HRQoL was also associated with poorer preoperative HRQoL for both patients and partners (Thomson et al 47).…”
Section: Resultsmentioning
confidence: 99%
“…A relative can be described as a hidden patient and life satisfaction of these individuals can often be lower than that of the actual patient [5]. It has been noted that the stress levels of relatives of patients hospitalized can be higher compared with the levels of the actual patients themselves [6] [7]. This may be due to the fact that the relatives of patients with a pacemaker may experience a heightened level of anxiety.…”
mentioning
confidence: 99%